SOSIALISASI MANAJEMEN WAKAF PRODUKTIF BERBASIS MASJID DI MASJID PATAL SENAYAN, JAKARTA SELATAN - Jaharuddin J.; Oneng Nurul Bariyah; Adi Mansah; Muhammad Fahmi; Syifa Fauziah; Fanny Amalia (JURNAL CEMERLANG: Pengabdian pada Masyarakat, 2023)
Al Insan Mosque, Patal Senayan, South Jakarta, continues to transform into a modern mosque, with innovative and creative programs based on the needs of the congregation. The implication requires a lot of financing and sustainable. The purpose of this community service is to socialize the concept of mosque-based productive waqf management, waqf is believed to be a support for modern mosque financing with various innovations and mosque program creativity. The method was carried out by preparing concepts, preparing modules, preparing human resources, and other preparations and conducting outreach to the administrators of the Al Insan mosque, Patal Senayan, South Jakarta, on Saturday, August 20 2022. This socialization resulted in a strong desire by the management to follow up on the management productive waqf funds at the Al Insan mosque, Patal Senayan, Jakarta.